2014
DOI: 10.1589/jpts.26.443
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Vaginal Pressures and Abdominal Muscle Thickness According to Childbirth Delivery Method during the Valsalva Maneuver

Abstract: [Purpose] The purpose of this study was to compare the effect of childbirth delivery method on vaginal pressure and abdominal thickness during the Valsalva maneuver (VAL). [Subjects] Thirty healthy female volunteers (26–39 years of age) were selected for this research. Their delivery histories were: nulliparous 10, vaginal delivery 10, and Cesarean delivery 10. None of the participants had a history of incontinence. [Methods] In the crook-lying position, a perineometer probe was inserted into the vagina and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…However, Faltin et al 22 ) analyzed 100 women at 3 and 30 months after their first delivery and reported that subsequent deliveries increase the risk of anal incontinence, especially in women with a sphincter defect after their first delivery. Kım et al 23 ) found significant differences between their nulliparous group and vaginal delivery group; and between their nulliparous group and Cesarean delivery group, and their results suggest that child birth delivery method changes the vaginal pressure. Peschers et al 24 ) used palpation, perineometry, and perineal ultrasound 3–8 days after delivery to evaluate PFM strength values of primiparous and multiparous women who had vaginal deliveries.…”
Section: Discussionmentioning
confidence: 93%
“…However, Faltin et al 22 ) analyzed 100 women at 3 and 30 months after their first delivery and reported that subsequent deliveries increase the risk of anal incontinence, especially in women with a sphincter defect after their first delivery. Kım et al 23 ) found significant differences between their nulliparous group and vaginal delivery group; and between their nulliparous group and Cesarean delivery group, and their results suggest that child birth delivery method changes the vaginal pressure. Peschers et al 24 ) used palpation, perineometry, and perineal ultrasound 3–8 days after delivery to evaluate PFM strength values of primiparous and multiparous women who had vaginal deliveries.…”
Section: Discussionmentioning
confidence: 93%
“…In their investigation, Kim et al [21] performed the Valsalva maneuver in three groups: nulliparous, women who had given birth naturally, and women who had a C-section. The authors performed ultrasound measurement of the muscle thickness, simultaneously assessing intravaginal pressure by means of a perineometer.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor dysfunction (PFD) can lead to mild or even devastating consequences such as urinary incontinence (UI), fecal incontinence (FI), pelvic organ prolapse (POP) and sexual problems 6 ) . The major known risk factors that contribute to PFD are pregnancy and childbirth, obesity, chronic obstructive pulmonary disease, and menopause 1 , 7 , 8 , 9 , 10 ) .…”
Section: Introductionmentioning
confidence: 99%